Lethal paralysis of Caenorhabditis elegans by Pseudomonas aeruginosa - Darby, Creg (The National Academy of Sciences, 1999)
Identification of host factors that interact with pathogens is crucial to an understanding of infectious disease, but direct screening for host mutations to aid in this task is not feasible in mammals. The nematode Caenorhabditis elegans is a genetically tractable alternative for investigating the pathogenic bacterium Pseudomonas aeruginosa. A P. aeruginosa toxin, produced at high cell density under control of the quorum-sensing regulators LasR and RhlR, rapidly and lethally paralyzes C. elegans. Loss-of-function mutations in C. elegans egl-9, a gene required for normal egg laying, confer strong resistance to the paralysis. Thus, activation of EGL-9 or of a pathway that includes it may lead to the paralysis. The molecular identity of egl-9 was determined by transformation rescue and DNA sequencing. A mammalian homologue of EGL-9 is expressed in tissues in which exposure to P. aeruginosa could have clinical effects.